THE KEY ROLE OF LANGUAGE IN THE GLOBAL AGE OF TRANSLATION - N'da, K (Research Journal of Literature, Languages and Linguistics, 2024)
This paper delves into the impact of globalization on contemporary translation in light of the rise of e-commerce and localization, automation, the prominence of supranational organizations, and time constraints, with emphasis on the centrality and marginalization of certain languages. The study employed a descriptive methodology and briefly outlined the historical background responsible for the emergence of globalization. A major finding of the paper is the successful use of machine translation in some institutes, while needing improvement in most cases. Additionally, translation memories have become pervasive in major organizations as a cost and timesaving measure. The paper also highlights the challenges associated with translating concepts and the potential endangerment of peripheral languages in the global translation system. Ultimately, this paper aims to elevate the status of translation studies as a scientific discipline and emphasizes its significance in understanding globalization.